2017
DOI: 10.1111/scs.12511
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of being a family member to an older person with diabetes receiving home care services

Abstract: It is important for personnel in home care services to consider patients' self-management skills and the family members' diabetes knowledge as key aspects in order to limit experiences of burden when the older person with diabetes has deteriorating health. The findings underscore that interaction with home care personnel skilled in managing diabetes helps family members feel secure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Various physical care activities provided by informal caregivers, restricted social life, and reciprocity of care have been reported by previous studies (Akgun-Citak et al, 2020;Bendixen et al, 2018;de Lima Lopes & Silva Marcon, 2013;Faronbi et al, 2019;Mthembu et al, 2016;Thai et al, 2016). Notwithstanding, motivation for care emanating from obeying instructions from the Bible as a belief system, non-availability of home for the aged, institutionalization and home care services, social workers, and occupational therapists as helpful support systems to reduce burden were some identified concepts that were unique to this study.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Various physical care activities provided by informal caregivers, restricted social life, and reciprocity of care have been reported by previous studies (Akgun-Citak et al, 2020;Bendixen et al, 2018;de Lima Lopes & Silva Marcon, 2013;Faronbi et al, 2019;Mthembu et al, 2016;Thai et al, 2016). Notwithstanding, motivation for care emanating from obeying instructions from the Bible as a belief system, non-availability of home for the aged, institutionalization and home care services, social workers, and occupational therapists as helpful support systems to reduce burden were some identified concepts that were unique to this study.…”
Section: Discussionmentioning
confidence: 60%
“…The healthcare needs of older adults with more than one disease, such as diabetes mellitus and hypertension, result in an increased financial burden for them, their informal caregivers, and the healthcare system as a whole (Ferris et al, 2018;He et al, 2018). In addition, the presence of a chronic condition in an older adult puts many limitations on his or her ability to manage the health condition alongside the various changes he or she may be exposed to as a result of ageing (Bendixen et al, 2018;de Lima Lopes & Silva Marcon, 2013), justifying the need for care support. Faronbi et al (2019) reported on providing physical care to older adults with NCDs similar to those provided by informal caregivers in this study, although they did not specify the NCDs suffered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation